Plant interactions and ergovaline concentration in mixture of Lotus tenuis and Schedonorus arundinaceus infected with the fungus Epichloë coenophiala - Petigrosso, Lucas R (2020)
Schedonorus arundinaceus (tall fescue) population can be infected by the endophyte fungus Epichloë coenophiala, responsible of livestock intoxication due to fungal alkaloids (i.e., ergovaline). The effects of ergovaline in pastures can be attenuated through dilution; this is, to interseed infected tall fescue (E+) with legumes, endophyte-free grass, or with both. Plant interaction and ergovaline concentration in mixture of tall fescue (E+) and Lotus tenuis, a forage legume, were investigated in replacement series experiments under defoliation conditions. The interaction between species was analysed through relative yield total (RYT) of the forage biomass, aggressivity index (AI), plant cover and ergovaline concentration. The work was performed in field conditions. Six cuttings were applied during the experimental period. Plant monocultures of each species were at a constant density of 80 pl/m2 , while mixtures ratios were 20:60, 40:40 and 60:20 pl/m² of L. tenuis and tall fescue, respectively. Mortality of L. tenuis and tall fescue plants was not observed. Tall fescues yield and plant cover, in monoculture and in mixture, were higher than in L. tenuis. RYT was higher than 1 for all mixtures. According to AI, in mixture, tall fescue was the dominant species and overcompensated the lower yield of L. tenuis. At the early Autumn, ergovaline concentration in monoculture was 1.637±0.594 ng/g, and in the 40:40 mixture was 0.407±0.109 ng/g. Forage production was higher in mixtures than in monocultures, and L. tenuis contributed to reduce ergovaline concentration. According to the results, 40:40 pl/m2 of tall fescue and L. tenuis was the best species combination. A positive effect of L. tenuis on growth of tall fescue mediated by nitrogen availability could have allowed the plant coexistence. Future experiments should analyse the variation of alkaloid concentration and forage production in tall fescue pastures, according to L. tenuis proportion, defoliation frequency and intensity under different seasons.